ISLAMIC SOCIAL REPORTING DETERMINATION IN THE MANUFACTURING INDUSTRY SECTOR LISTED IN INDONESIA SHARIA STOCK INDEX - Soeharjoto Soekapdjo (Integrated Journal of Business and Economics (IJBE), 2021)
Aims of this study is to know about Islamic Social Reporting determination at manufacturing  industry sector listed on Indonesia Sharia Stock Index, with the exchange rate and inflation as moderating variables. Panel data regression is used as a method with Islamic Social Reporting  as a dependent variable and Return on Equity, Current Ratio, Debt to Equity Ratio, Firm Size as an independent variables, while inflation and exchange rates used as a moderating variables. Sampling is from manufacturing industrial companies listed in Indonesia Sharia Stock Index used purposive sampling in 2013-2018. Sourced data from Financial Services Authority, Central Statistics Agency and Bank Indonesia. Result shown that Return on Equity with inflation moderation has a positive and significant effect on Islamic Social Reporting, Current Ratio has a positive and significant effect on Islamic Social Reporting, and Debt to Equity which is moderated by the exchange rate has a positive and significant effect on Islamic Social Reporting.  However, the inflation moderated Firm Size is not significant to the Islamic Social Reporting. In order to get blessings, manufacturing industry needs awareness from companies to implement the Islamic Social Reporting, Financial Services Authority implements and develops ISR indicators for all sectors, investors fully apply sharia principles to get blessings, and people buy products that are halal and toyiban, also government maintain exchange rates stability and inflation.